2022
DOI: 10.18502/kme.v2i3.11850
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Folic Acid in Chronic Kidney Disease Patients With Anemia

Abstract: Chronic kidney disease (CKD) is defined as decreasing kidney function (GFR < 60 ml/minute/1.73 m2 ) for more than 3 months. Anemia is a common complication of CKD due to a decrease in the hormone erythropoietin related to hemoglobin levels. One of the anemia therapies involves using folic acid. Folic acid helps the process of nucleoprotein synthesis and erythropoiesis maintenance. The objective of this study was to determine the pattern of folic acid applied to CKD patients with anemia at University of Muha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…A study by Garg et al (2001) conducted among HD patients in Unites States reported that lower level of folic acid has been seen in HD patients due to malnutrition and folate loss through dialysate [29]. Therefore, folic acid intake by HD patients can help to reduce cardiovascular disease by reducing the serum homocysteine levels [30,31]. Besides that, insufficient anemia management with erythropoietin (EPO) was also observed.…”
Section: Plos Onementioning
confidence: 99%
“…A study by Garg et al (2001) conducted among HD patients in Unites States reported that lower level of folic acid has been seen in HD patients due to malnutrition and folate loss through dialysate [29]. Therefore, folic acid intake by HD patients can help to reduce cardiovascular disease by reducing the serum homocysteine levels [30,31]. Besides that, insufficient anemia management with erythropoietin (EPO) was also observed.…”
Section: Plos Onementioning
confidence: 99%
“…Cardiovascular abnormality is the most concerning risk factor that leads to CKD. Generally, CKD can be divided into five stages, where End-Stage Renal Disease (ESRD) is a condition where GFR value is less than 15 ml/minute [1]. Initially, in patients with early stage CKD (stage 1-2), patients are mostly asymptomatic without any finding suggesting metabolic disturbances.…”
Section: Introductionmentioning
confidence: 99%